2020
DOI: 10.1002/cctc.202000889
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth‐Decorated Silicon Photocathodes for CO2‐to‐Formate Solar‐Driven Conversion

Abstract: The integration of metal-based catalysts onto semiconducting electrodes provides a real benefit for the CO 2 electrochemical conversion because it allows the electrochemical process to be activated by photogenerated electrons. In that context, we report here that silicon photocathodes modified with electrodeposited Bi nanostructures are highly active for the photoelectrocatalytic conversion of CO 2 to formate. Through the consumed electrical charge and the electrodeposition time, it is possible to finely contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Photo/ electrodeposition provides a straightforward catalyst deposition technique that is well-matched for applications in PEC CO 2 RR. 36,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] In the following sections, we explore recent and noteworthy research in the field of PEC CO 2 RR employing various co-catalysts organized by the types of reduction products generated. In addition, we categorized representative research papers, considering the methods of co-catalyst deposition, which encompass PVD, drop-casting, and photo/electrodeposition.…”
Section: Investigation Of Co-catalysts For Selective Co 2 Reduction R...mentioning
confidence: 99%
See 1 more Smart Citation
“…Photo/ electrodeposition provides a straightforward catalyst deposition technique that is well-matched for applications in PEC CO 2 RR. 36,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] In the following sections, we explore recent and noteworthy research in the field of PEC CO 2 RR employing various co-catalysts organized by the types of reduction products generated. In addition, we categorized representative research papers, considering the methods of co-catalyst deposition, which encompass PVD, drop-casting, and photo/electrodeposition.…”
Section: Investigation Of Co-catalysts For Selective Co 2 Reduction R...mentioning
confidence: 99%
“…The co-catalyst for HCOOH production can be deposited onto the Si surface through the photo/electrodeposition of Sn, Bi, and Ni@In. [66][67][68][69][70][71][72] novel photocathode for CO 2 reduction towards HCOO − production, which involved the modification of Bi NPs on GaN NW arrays situated on a p-n junction Si wafer (denoted as Bi/ GaN/Si, Fig. 11a).…”
Section: Pec Co 2 Reduction To Formic Acid (Hcooh)mentioning
confidence: 99%
“…f) Photoelectrocatalytic reduction of CO 2 to formate from electrodeposited Bi 2 O 3 nanostructure-modified Si(100) photocathodes and g) LSVs at 20 mV s –1 of the photocathode before and after 30 min electrolysis at −1.03 V in CO 2 -saturated 0.5 M KHCO 3 solution. Reprinted with permission from ref . Copyright 2020 Wiley-VCH.…”
Section: Si Photocathodesmentioning
confidence: 99%
“…20 Besides the HER, great attention has been paid to metal-modified Si(100) photocathodes for the CO 2 reduction. In particular, photocathodes modified with Bi 21,22 and Sn 23 nanostructures have been considered for the photoelectrocatalytic conversion of CO 2 to formate with the first ones showing superior performance (Figure 3f,g).…”
Section: (Semi-) Noble Metalsmentioning
confidence: 99%
“…The high HCOOH yield was reported to be mainly attributed to an effective proton transfer between the BNAH proton carrier and Ru II molecular catalyst through a covalent bond connection under illumination. [9] Especially, co-catalysts such as Bi, [10] In, [11] Ag, [12] or Au, [4] modified on the surface of the semiconductor, can effectively convert CO 2 to more C-products in an aqueous PEC cell. For example, DuChene et al demonstrated that the plasmon-induced hot electrons from Au nanoparticles improved the selectivity of CO product, driving solarto-fuel energy conversion.…”
Section: Introductionmentioning
confidence: 99%